Facile synthesis of graphitic carbon nitride from acetic acid pretreatment to activate persulfate in presence of blue light for photocatalytic removal of metronidazole. (August 2021) - Sudhir Ekande, Onkar; Kumar, Mathava
Abstract: Activation of persulfate (PS) in presence of blue LED light ( λ max ∼454 nm) using acetic acid modified graphitic carbon nitride (ACN) was investigated. Usage of acetic acid had improved the specific surface area (SSA, 21.89 m 2 g −1 ) of ACN compared with pristine graphitic carbon nitride (GCN) and it also reduced interfacial charge transfer resistance in ACN. Subsequently, photocatalytic removal of metronidazole (MET) was investigated using ACN. It was observed that upward shift in the conduction band (CB) in ACN produced the reduction of PS to form sulfate radicals (SO4 .- ) (CB of ACN (−1.25 V vs normal hydrogen electrode (NHE); Bandgap = 2.77 eV) and GCN (−1.23 V vs NHE; Bandgap = 2.73 eV)), which enhanced the MET removal. Moreover, batch experiments were conducted to quantify the effects of PS dosage (0.08–0.40 g L −1 ), ACN dosage (0.20–2 g L −1 ), light intensity (15–45 W), and pH (2–13.50). ACN (1 g L −1 ) and GCN (1 g L −1 ) with 0.16 g L −1 of PS have shown 100% and 76.1% MET (Co -10 mg L −1 ) removal within 300 min, respectively, and the removal followed zero-order kinetics (k ∼2.39 mg L −1 h −1 ). However, MET mineralization was approximately 30% with ACN. MET removal had decreased with increase in pH and almost complete inhibition was observed at pH ∼12. Overall, it was identified that SO4 .- was the major reactive species whereas holes (h + ) in the valence band (VB) of ACN (1.52 V vs NHE) played a minor role in MET removal. Graphical abstract: Image 1 Highlights: Mentronidazole (MET) removal by activation of persulfate using acetic acid modified carbon nitride (ACN) in blue light. Pretreatment with acetic acid increases the specific surface area of g-C3 N4 from 4.30 to 21.89 m 2 g −1 . Increase in reducing potential and interfacial charge transfer of ACN. Effects of persulfate dose, ACN dose, pH, light intensity, and competitive anions on MET removal were examined.